2016
DOI: 10.1016/j.ygyno.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression is associated with tumor-infiltrating T cells and favorable prognosis in high-grade serous ovarian cancer

Abstract: PD-L1 is primarily expressed by macrophages in ovarian cancer and is strongly associated with both cytolytic and regulatory TIL subsets, resulting in a net positive association with survival. Tumors containing PD-L1(+) macrophages appear caught in an immunological stalemate that may require multi-pronged immunotherapy to alleviate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
252
6
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(296 citation statements)
references
References 40 publications
31
252
6
7
Order By: Relevance
“…Several researches also described similar association. 23,31,32 This correlation was in accordance with the previous finding that IFNg, expressed by activated CD8 C T cells, can induce PD-L1 expression in the surrounding tumor cells. 33 Moreover, seven patients (Table 2) with absent or focal TILs still presented PD-L1 positivity.…”
Section: Discussionsupporting
confidence: 92%
“…Several researches also described similar association. 23,31,32 This correlation was in accordance with the previous finding that IFNg, expressed by activated CD8 C T cells, can induce PD-L1 expression in the surrounding tumor cells. 33 Moreover, seven patients (Table 2) with absent or focal TILs still presented PD-L1 positivity.…”
Section: Discussionsupporting
confidence: 92%
“…PD-1/PD-L1 blockade caused tumor regression in a syngeneic EOC mouse model, thus supporting the relevance of this regulatory pathway in ovarian carcinogenesis (38).…”
Section: Epithelial Ovarian Cancersupporting
confidence: 52%
“…Conflicting data emerge from the literature about the prognostic relevance of PD-1 and PD-L1 expression in EOC and these discordant results may reflect different techniques for PD-1 and PD-L1 assessment, different cut-off values for tumor cell staining, as well aspatients' heterogeneity (34)(35)(36)(37)(38).…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%
“…For example, in ovarian cancer, the differential expression of immunological markers related to the PD-1/PD-L1 pathway in blood can be used as potential diagnostic and prognostic markers [13]. PD-L1 is also expressed by macrophages in ovarian cancer and is strongly associated with both effector and regulatory tumour infiltrating lymphocyte (TIL) subsets [14]. Interestingly, Yang et al revealed a previously unrecognized mechanism through which chemotherapy induces tumour immune evasion via the up-regulation of PD-L1 in bone marrow stromal cells, providing new evidence for the combination of chemotherapy and anti-PD-L1/PD-1 as an effective strategy for the treatment of lymphoma and other cancers [15].…”
Section: Introductionmentioning
confidence: 99%